O português de Timor Leste : contribuições para o estudo de uma variedade emergente - Albuquerque, Davi Borges de (2011)
Portuguese has been the official language of East Timor since 2002. With the Portuguese language transplanted to former colonies of Portugal, varieties of the language emerged in each one of the different colonies. The present paper aims to give a brief history of the Portuguese language in East Timor (2), and analyze the East Timorese variety of Portuguese on different linguistic levels: phonology (3), morphosyntax (4), lexicon and semantics (5) in order to show the existence of this variety and to aid its preservation.